(untitled) (PJDOL, 2023)
The main objective of the study was to investigate the assessment literacy of university teachers. The study was quantitative in nature. A survey was conducted to investigate the assessment literacy of regular teaching faculty of universities. A total of 5755 in public and private sector general universities in Lahore, Pakistan constituted the population of the study. A sample of 500 university teachers was randomly selected.